Development of an artificial synovial fluid useful for studying Staphylococcus epidermidis joint infections - Stamm, Johanna; Weißelberg, Samira; Both, Anna; Failla, Antonio Virgilio; Nordholt, Gerhard; Büttner, Henning; Linder, Stefan; Aepfelbacher, Martin; Rohde, Holger (Frontiers in Cellular and Infection Microbiology, 2022)
Staphylococcus epidermidis is a major causative agent of prosthetic joint infections (PJI). The ability to form biofilms supports this highly selective pathogenic potential. In vitro studies essentially relying on phenotypic assays and genetic approaches have provided a detailed picture of the molecular events contributing to biofilm assembly. A major limitation in these studies is the use of synthetic growth media, which significantly differs from the environmental conditions S. epidermidis encounters during host invasion. Building on evidence showing that growth in serum substantially affects S. epidermidis gene expression profiles and phenotypes, the major aim of this study was to develop and characterize a growth medium mimicking synovial fluid, thereby facilitating research addressing specific aspects related to PJI. Using fresh human plasma, a protocol was established allowing for the large-scale production of a medium that by biochemical analysis matches key characteristics of synovial fluid and therefore is referred to as artificial synovial fluid (ASF). By analysis of biofilm-positive, polysaccharide intercellular adhesion (PIA)-producing S. epidermidis 1457 and its isogenic, PIA- and biofilm-negative mutant 1457-M10, evidence is provided that the presence of ASF induces cluster formation in S. epidermidis 1457 and mutant 1457-M10. Consistent with the aggregative properties, both strains formed multilayered biofilms when analyzed by confocal laser scanning microscopy. In parallel to the phenotypic findings, expression analysis after growth in ASF found upregulation of genes encoding for intercellular adhesins (icaA, aap, and embp) as well as atlE, encoding for the major cell wall autolysin being responsible for eDNA release. In contrast, growth in ASF was associated with reduced expression of the master regulator agr. Collectively, these results indicate that ASF induces expression profiles that are able to support intercellular adhesion in both PIA-positive and PIA-negative S. epidermidis. Given the observation that ASF overall induced biofilm formation in a collection of S. epidermidis isolates from PJI, the results strongly support the idea of using growth media mimicking host environments. ASF may play an important role in future studies related to the pathogenesis of S. epidermidis PJI.